2016
DOI: 10.6024/jmbai.2016.58.1.1895-05
|View full text |Cite
|
Sign up to set email alerts
|

Check list of fishes of the Gulf of Mannar ecosystem, Tamil Nadu, India

Abstract: Gulf of Mannar Ecosystem (GOME) covers an area spread over Rameswaram and Kanyakumari for about 19000 km 2 and lies between 78°11'E and 79°15' E longitude and 8°49'N and 9°15'N latitude. The 21 coral islands form a network of habitats for different kinds of fishes and marine organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Ganesh and Geetha (2017) investigated elasmobranch by-catch diversity and reported 24 species of elasmobranch belonging to 6 orders, 10 families and 11 genera in the same region. Joshi et al (2016) reported 51 species of sharks belonging to 25 genera, 15 families and 7 orders from the Gulf of Mannar. Thilaka et al (2017) reported 45 species of sharks from the same region.…”
Section: Introductionmentioning
confidence: 99%
“…Ganesh and Geetha (2017) investigated elasmobranch by-catch diversity and reported 24 species of elasmobranch belonging to 6 orders, 10 families and 11 genera in the same region. Joshi et al (2016) reported 51 species of sharks belonging to 25 genera, 15 families and 7 orders from the Gulf of Mannar. Thilaka et al (2017) reported 45 species of sharks from the same region.…”
Section: Introductionmentioning
confidence: 99%
“…2). Jones and Kumaran (1980), Manna and Goswami (1985), Sethi et al (2013), Rajan et al 2013, Joshi et al (2016), Kar et al (2017) and Kayalvizhi et al (2018) reported one more species namely H. marginatus from Indian waters but their distribution is mostly restricted to the Red Sea and the Persian Gulf in the western Indian Ocean (Carpenter et al 1997). Such reports from Indian waters are questionable which might have been misidentified with morphologically similar species occurring in the area.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution maps of comPaGno (1984,2001) show an absence of the species from the east coast of the Indian subcontinent. However, later records of C. leucas from the east coast of India were provided by raJe et al ( 2002 2009) for the Pulicut Lagoon (see Table 7) and by Joshi et al (2016) for the Gulf of Mannar. Joshi et al (2018) reported C. leucas from India's southwest coast.…”
Section: Distribution In the Northern Indian Oceanmentioning
confidence: 99%